Carcinoma Caecum coexistent with Tuberculosis : a case report (Faculty of Medicine Universitas Indonesia, 2005)
Tubercular lesion may coexist with malignancy in various sites resulting in dfficulties in diagnosing the conditions. A case of carcinoma caecum associated with tubercular lesion in the same site is reported. The patient have completed the antitubercular therapy and is now on regular anticancer chemotherapy. Till now the patient is doing fine. (Med J Indones 2005; 11: 128-30) Keywords : Carcinoma Caecum, Intestinal Tuberculosis, Management